Media Qualifications Flashcard Contextual-Based in Improving Bima Literacy in Elementary Schools - Fauziah, Naila; Khatimah, Khusnul; Khairunnufus, Nastri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Bima Script, also known as Aksara Mbojo, is one of the local cultural heritages that has been gradually neglected by the younger generation, particularly at the elementary school level. The lack of teaching materials and engaging learning methods has resulted in low student motivation to learn local scripts. This study aims to develop and assess the feasibility of context-based flashcards as an alternative learning media for teaching the Bima Script in elementary schools. The research employed a Research and Development (R&D) approach with the ADDIE model (Analyze, Design, Develop, Evaluate). The participants were elementary school students in Rabakodo Village, with validation conducted by four experts, consisting of two media experts and two material experts. The assessment instrument used a 1–4 scale covering visual design, technical aspects, usability, contextual relevance, content feasibility, language, and alignment with learning objectives. The validation results indicated an average score of 94.16 percent for media aspects and 98.33 percent for material aspects, both categorized as “highly feasible.” The flashcard media proved to be simple, attractive, easy to use, and contextually relevant to students’ daily experiences, making it effective for introducing the Bima Script while supporting local cultural preservation. Therefore, context-based flashcards can serve as a practical learning medium that contributes to strengthening students’ cultural identity.